Predicting the timing of the peak of the pubertal growth spurt in elite male youth soccer players: evaluation of methods - James Parr; Keith Winwood; Emma Hodson-Tole; Frederik J. A. Deconinck; Les Parry; James P. Hill; Robert M. Malina; Sean P. Cumming (Taylor & Francis Group, 2020)
Background Three commonly used non-invasive protocols are implemented to estimate the timing at which PHV most likely occurs. Accurate estimation of circumpubertal years can aid in managing training load of adolescent athletes. Aim Three protocols were compared against observed age at PHV: an estimate of 13.8 ± 1.0 years - generic age at PHV (from longitudinal measures); an estimate based on the maturity offset equation, predicted age at PHV ±1.0 year; a window of PHV based on 85-96% of predicted adult height at time of observation. Subjects and methods A final sample of 23 (from 28) adolescent male participants were selected from the academy of an English Premier League club. Anthropometric measures were collected across five playing seasons; age at PHV was estimated with Super-Imposition by Translation and Rotation (SITAR). The three protocols were compared based on measures at 13.0 years. Results and Conclusions: An age window based on predicted maturity offset did not improve estimation of PHV compared to generic age method; however, the percentage of predicted adult height window showed improvement in performance shown by the following results. Predicted age at PHV correctly assigned 15 participants (65%) as experiencing PHV, while the percentage height correctly assigned 17 participants (74%). Generic age and predicted age at PHV correctly predicted observed age at PHV for 14 participants (61%), percentage of adult height window correctly predicted 22 participants (96%).